The professional approach in the philosophy of knowledge At John Dewey (Journal of the College of Basic Education, 2022)
The process of knowledge according to John Dewey is an intellectual path that includes psychological laws that are specific to the mind, and it is a kind of activity practiced by the soul, and therefore a certain type of self-movement necessitated its establishment in the first place in the material facts in natural science, and all these facts are known by a mind, and therefore they are within the scope of competence. Psychology in a way, therefore, psychology is a central science whose subject is knowledge.Dewey believes that pragmatic knowledge is not primary and does not precede experience, but it stems from the experience itself (experience), and it is a fruit resulting from the participation of the mind in the course of life, as knowledge intervenes in the world, changes it and directs it.